Competências necessárias para a gestão do orçamento público na Universidade Federal do Pará - NOGUEIRA, Francisco Jorge Rodrigues (Universidade Federal do Pará, 2019)
The mapping of individual competences for implementation of the public budget was applied in the Federal University of Para, Northern Brazil. This research considered the technical administrator federal and freeholder employees that develop their activities in the units of the Upper Management, supplementary units, University Hospitals and in the Planning Coordination, management and Evaluation (PCMEs) of Institutes, Centers and Campuses. The range of information were obtained from official documents based on documentation analysis technique, allowing defining specific characteristics, establishing relations between the several variables linked to their responsibilities. The qualitative approach considered the subjectivity in the interpretation, attributing general meanings to the phenomena to identify sectorial and individual competences linked with the strategic objectives of the institution. Quantitative analysis used the essential individual competences for the organization, translated in numbers and based on the questionnaires results. The first and second phases of the research identified and validated the sectorial and individual competences. The third and fourth phases defined the importance degree of competence to the unit and the domain degree of the employees in those competences. The last phase was generated the Training Degree Request (TDR) for the technical administrator federal and freeholder employees. In general, the results indicated the TDR related to the individual competences, but the main result was the acquirement of the TDR related to units of the Upper Management, supplementary units, Institutes, Centers and Campuses and the University Hospitals. This final TDR will could support the development of programs focused in the sectors that request training in the budget, financial and accounting implementation area of the Federal University of Para